Edukasi Pengendalian Lalat dan Penerapan Alat Fly Grill sebagai Upaya Pencegahan Penyakit Foodborne di Kantin UNMA Banten - Heny Sasmita (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2023)
Food safety is a crucial aspect in campus environments, particularly in canteen areas that serve ready-to-eat food. The presence of flies as mechanical vectors of foodborne diseases such as diarrhea, typhoid, and dysentery is still commonly found in the canteen of Mathla’ul Anwar University (UNMA) Banten. This community service activity aimed to increase the knowledge and awareness of canteen managers about the dangers of flies and to introduce the use of fly grill devices as a simple solution to prevent food contamination. The methods included interactive education, demonstration of fly grill production and installation, and evaluation through pre-test and post-test. The results showed a 24% increase in participants' knowledge and a behavioral shift toward more hygienic food serving practices. Most participants found the fly grill effective, easy to create, and applicable for independent use. This activity is expected to support the establishment of fly-free, hygienic canteens as part of foodborne disease prevention efforts in the campus setting.